A U-MODEL BASED NONLINEAR ADAPTIVE CONTROL FOR UNDERACTUATED MULTIVARIABLE UNMANNED MARINE VEHICLES - ALI HUSSAIN, NUR AFANDE (2021)
In this study, underactuated coupled nonlinear adaptive control for multivariable unmanned marine vehicles platform were studied, designed, developed, and tested. Designing a controller that is suitable for both surface and underwater unmanned marine vehicle is challenging tasks due to unstructured marine environment, highly nonlinear due to the hydrodynamics and parameters interaction plus with the external disturbances. Coupled nonlinear adaptive control using U-Model based internal model control (IMC) approach can be implemented to overcomes these challenges. IMC approach offer a good disturbances rejection capability. The method implements coupled nonlinear identification via U-Model which able to model the system with minimum error. Then, the controller is formularised using Newton Raphson method as a representation of the inverse of the U-Model.